FAKTOR-FAKTOR YANG MEMPENGARUHI KELUHAN PENGLIHATAN PADA REMAJA DI SMA KATOLIK CENDRAWASIH MAKASSAR - Alia Andriany (Stikes Graha Edukasi Makassar, 2020)
Adolescence is a period of transition from childhood to adulthood. Where adolescents are often faced with various problems related to learning achievement, electronic media, and complaints on the sense of sight. This study aims to determine the factors that influence sight complaints in adolescents at Cendrawasih Catholic High School Makassar. The research design used a cross-sectional method, with a population of 281 people using a proportional stratified random sampling technique. The results showed that from 162 respondents, 86 respondents (79.8%) had complaints of vision problems, 126 respondents (119.2%) used gadgets, and 85 respondents (78.9%) read while sleeping. From the results of the Fisher's exact test it is known that watching television has a value of p = 0.006, reading while sleeping has a value of p = 0.007, and using gadgets has a value of p = 0.000 which means that the p value ? 0.05 then H0 is rejected and Ha is accepted so it can be concluded that there is a relationship between watching television, using gadgets, and reading while sleeping with vision complaints in adolescents at Cendrawasih Catholic High School Makassar. From the results of the study it was suggested to health workers to provide education about the proper and appropriate use of social media so that adolescents are able to avoid and overcome vision complaints and agencies are expected to cooperate with health institutions in monitoring adolescent health developments